Increased Procoagulant Response of Monocytes from Patients with Familial Mediterranean Fever - Courillon-Mallet, Anne; Bevilacqua, Michael; Wautier, Jean-Luc; Dervichian, Michel; Cattan, Daniel; Caen, Jacques (Thrombosis and Haemostasis, 1986)
Familial Mediterranean Fever (FMF) is an inherited disease of unknown etiology characterized by recurrent inflammatory episodes. Circulating fibrin was found in patients with FMF in absence of clinical manifestation of thrombosis and was statistically less frequently observed in patients treated with colchicine. These results suggest a cellular dysfunction. Therefore, we examined the procoagulant activity (PCA) of isolated mononuclear leukocytes and purified monocytes from FMF patients (n = 20). No PCA was detectable on freshly-isolated monocytes. After several hours of culture, FMF monocytes contained more PCA than control cells and the difference was more marked after endotoxin stimulation. Data obtained with coagulation factor-deficient plasma and anti-human apoprotein III antiserum indicated that the enhanced PCA in FMF monocytes is thromboplastin-like. Lysozyme and interleukin 1 production by monocytes were similar in patients and controls. The increased monocyte PCA appears to be due to an intrinsic and selective higher responsiveness of monocytes.
Keywords: Monocytes; Procoagulant activity; Familial Mediterranean Fever; Interleukin 1